1998
DOI: 10.1128/jb.180.3.680-689.1998
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Binding Protein-Dependent ABC Transporter: Molecular and Biochemical Analysis of the Trehalose/Maltose Transport System of the Hyperthermophilic Archaeon Thermococcus litoralis

Abstract: We report the cloning and sequencing of a gene cluster encoding a maltose/trehalose transport system of the hyperthermophilic archaeonThermococcus litoralis that is homologous to themalEFG cluster encoding the Escherichia colimaltose transport system. The deduced amino acid sequence of themalE product, the trehalose/maltose-binding protein (TMBP), shows at its N terminus a signal sequence typical for bacterial secreted proteins containing a glyceride lipid modification at the N-terminal cysteine. The T. litora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…Moreover, although a statistical model [10] predicted that four of the six MBPs were likely to be insoluble in E. coli, we found that all of them were highly soluble at 37 ‡C. Tli MBP does not bind to amylose resin [11], but all of the other MBPs were quantitatively retained on an amylose column, indicating that they were properly folded (data not shown).…”
Section: Overproduction Of Unfused Mbps In E Colimentioning
confidence: 68%
“…Moreover, although a statistical model [10] predicted that four of the six MBPs were likely to be insoluble in E. coli, we found that all of them were highly soluble at 37 ‡C. Tli MBP does not bind to amylose resin [11], but all of the other MBPs were quantitatively retained on an amylose column, indicating that they were properly folded (data not shown).…”
Section: Overproduction Of Unfused Mbps In E Colimentioning
confidence: 68%
“…Binding of [ 14 C]-maltose was strongly inhibited by a 10-fold excess of unlabelled maltose (76%), weakly by maltotriose (44%) and not at all by trehalose (0%). This binding activity is therefore specific for maltose/maltodextrin, and it differs from the maltose/trehalose-binding protein found in many other organisms (Xavier et al, 1996;Horlacher et al, 1998;Wassenberg et al, 2000). As S. solfataricus can grow on trehalose as sole carbon and energy source, and [ 14 C]trehalose binds to all examined ConA fractions ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Such systems have also been found for the uptake of sugars in other archaea as, for instance, the uptake of maltose and trehalose in the hyperthermophilic Thermococcus litoralis (Xavier et al, 1996). The genes encoding this system have been cloned and sequenced and shown to be homologous to the maltose transporter of Escherichia coli, MalEFGK (Horlacher et al, 1998). Recently, three ABC transporters of Haloferax volcanii have been functionally characterized and shown to be essential for nitrate respiration (Wanner and Soppa, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Low level accumulation of trehalose in Pyrococcus horikoshii and P. furiosus, and high levels of trehalose in Thermococcus litoralis, appears to derive exclusively from yeast extract in the medium. In these organisms, trehalose appears to be taken up from yeast extract through a high affinity ABC maltose/trehalose transporter (Horlacher et al, 1998;Koning et al, 2002). The hyperthermophilic crenarchaeote Pyrobaculum aerophilum, accumulates trehalose exclusively at its optimum growth temperature and salinity, unlike other hyperthermophilic archaea.…”
Section: Compatible Solutes Of Thermophiles and Hyperthermophilesmentioning
confidence: 99%